EDMODO : AN INNOVATIVE BLENDED-LEARNING TO ENHANCE STUDENTS’ ENGLISH ABILITY - Rifai, Dian Muhammad (JURNAL GAUNG INFORMATIKA, 2017)
Edmodo is one of educational technologies that aims at providing teachers with tools to help them communicate with their students and parents. It can be used to help students to raise their motivation in learning English especially in reading ability. This research aims to identify the potentials and challenges of using Edmodo on reading ability. This research used qualitative descriptive design. This research is paper based research. The researcher carried out the information about Edmodo tools then discussed with the research before. The researcher focus on the benefit of using edmodo in teaching learning process. The writer carries out a qualitative research inthis research. The result of the research shown that Edmodo can be engage effectively to create inovative blended-learning. First, Edmodo is a useful and helpful tool to teach and to learm English ability particularly in reading ability. Second, Edmodo helps teachers to control and maintain their students’ learning process. Third, Edmodoprovides the overview and transparancy of students’ progress and achievement. Fourth, Edmodo provides a feature for the students to build good communication with theirteacher.